Ratels on the Lomba: The story of Charlie Squadron - Scherman, Jean Pierre (Scientia Militaria - South African Journal of Military Studies, 2021)
Ratels on the Lomba bursts onto the page like a shot from a cannon, full of dramatic scenes of warfighting, with blood flowing and where bullets are pinging off armour plates. It is, however, far more than just another book on the Border War (1966–1989). If you are looking for a feel-good book, describing how the valiant South African Defence Force (SADF) fought and won, then look elsewhere. This book tells the story of a small sub-unit, fewer than 100 men strong, from the perspective of the soldier on the ground, where the bullet meets the meat. It reads more like a horror story than like a war story – but we will get back to that.